LIVER DAMAGE IN HELLP SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
HELLP Syndrome (Hemolysis, Elevated Liver Enzymes, Low Platelet Count) – a severe complication of pregnancy associated with preeclampsia. This condition involves liver injury, significantly increasing the risk of maternal and perinatal mortality. HELLP syndrome is classified among the most severe pregnancy complications requiring urgent medical intervention. According to the World Health Organization, the prevalence of this syndrome ranges from 0.1% to 0.8% of all pregnancies; however, among women with preeclampsia and eclampsia, this figure reaches 10–20% [6]. In cases of delayed diagnosis and lack of timely treatment, maternal mortality rates can reach up to 25% [1]. In recent decades, an increase in hypertensive disorders during pregnancy has been observed, making the HELLP syndrome particularly significant. Studies show that approximately 15% of cases remain undiagnosed, which increases the risk of complications such as hepatic rupture, acute renal failure, and disseminated intravascular coagulation (DIC) [8]. The syndrome is more frequently diagnosed in women over 30 years old, with chronic illnesses, obesity, and multiple pregnancies [5].